A New Risk Score Based on Lipid Indicators for Patients with Advanced Hepatocellular Carcinoma - Wei X; Guo Z; Zhang T; Liang J (Journal of Hepatocellular Carcinoma)
Xing Wei,1 Ziwei Guo,2 Tingting Zhang,3 Jun Liang1 1Department of Medical Oncology, Peking University International Hospital, Beijing, People’s Republic of China; 2Department of Medicine, Double Crane Runchuang Technology (Beijing) Co., Ltd, Beijing, People’s Republic of China; 3Department of General Surgery, Beijing Friendship Hospital, Capital Medical University, State Key Laboratory of Digestive Health, National Clinical Research Center for Digestive Diseases, Beijing, People’s Republic of ChinaCorrespondence: Jun Liang, Email Junl1959@163.comBackground: The prognosis is extremely troubling in advanced hepatocellular carcinoma (HCC). Prognostic scores have been developed. Yet, the positive predictive values might appear inadequate. This retrospective study aimed to develop a quick and efficient risk score to assess prognosis and clinical response.Methods: A total of 391 hCC patients were enrolled and were divided into training and validation groups between 2015 and 2024. Patients were separated into high-risk and low-risk groups using X-tile software. Using the COX proportional risk model analysis method, we then created a risk score and examined them using Kaplan-Meier, time-dependent receiver operating characteristics (ROC) curve, and nomogram analysis.Results: In predicting overall survival (OS), free fatty acid/high-density lipoprotein cholesterol (FFHL), tumor size, and BCLC stage were independent prognostic variables. A new risk score was developed just above and used as a prognostic factor (p < 0.001 in the training and validation groups) and had a high time-dependent ROC for progress-free survival (PFS) (area under the curve [AUC] 0.688– 0.789 in the training group; AUC 0.592– 0.741 in the validation group) and OS (AUC 0.812– 0.918 in the training group; AUC 0.692– 0.981 in the validation group). In comparison to the best overall response (BOR), the score offered a more accurate evaluation of durable clinical benefit (DCB) (p < 0.001 in the training and validation group; p = 0.061 vs 0.001 in the training and validation group).Conclusion: A new score based on lipid markers is a useful tool for evaluating prognosis and distinguishing patients with DCB.Keywords: hepatocellular carcinoma, survival, prognosis, clinical response, risk score